Can lower(ed) expert opinions lead to better consumer ratings?: The case of Michelin stars - LI, X. (Institutional Knowledge at Singapore Management University, 2022)
Expert opinion exerts tremendous influence on the purchase journey, but its effect on overall consumer experience is ambiguous as it can give rise to both "expectation" and "reputation" effects. This paper explores the effect of expert opinions on consumer experience via the lens of consumer reviews in the restaurant industry, where the expert opinions are conveyed by Michelin stars. The paper uses a unique data set based on the Michelin Guide for Great Britain & Ireland from 2010-2020. The data include consumer reviews on TripAdvisor for all restaurants that were awarded Michelin stars during this period and a large pool of potential control restaurants. We apply two synthetic-control-based methods to estimate the effect of Michelin star changes on the sentiment and content of consumer reviews. We find that decreases in Michelin stars improve consumer review ratings. We examine three potential explanations for this finding. First, the positive expectation effect of lowered expert opinions outweighs the negative reputation effect. Second, there could be a change in the customer mix. Third, there may be changes on the supply side, e.g., in service levels. We find support for the first explanation, rule out the second but cannot entirely rule out the third. The analysis of review content further shows that a loss in Michelin stars leads consumers to become less focused on value and become less demanding regarding service. We discuss the implications of our findings for restaurant managers, the Michelin Guide, and other businesses that provide experience goods.